Experimental investigation of dual operation EMC-fed antenna having dual-perturbed structures - Esa, Mazlina; Ismail, Mohd. Khairul Hisham; Murad, Noor Asniza; Othman, Rosmawati (IEEE, 2004)
This paper presents the experimental investigation of a dual-operation antenna operating in the L-band region. The basis of the design is the basic rectangular patch. The patch is perturbed with embedded two L-section structures. The chosen frequencies are 1.575 GHz for Giobal Positioning System (GPS) satellite receiver and 1.8 GHz for Global System for Mobile (GSM). The antenna has been measured for its one and two-port performance. Optimum feed location was determined to be at the 14.5 mm location from the antenna edge. It was found that the antenna operates well near the designed frequency of operations.